Transfer Pricing And Tax Malfeasance: Perspectives From The Malaysian Inland Revenue Board - Saw, Soo Fang (2023)
The objectives of the study are: first, to understand the issues with measures taken by IRBM to detect the areas of tax malfeasance among Malaysian MNEs when setting up transfer pricing. Second, to determine the courses of action taken by IRBM to overcome tax malfeasance by MNEs and lastly, to investigate the reason behind the need for an implementation of law or regulations or activities to deter future occurrences of tax malfeasance.